(untitled) (Research, Society and Development, 2022)
The present study aims to diversify the humanized delivery process, focusing mainly on the assistance of the nursing team in such a situation. For this, the factors involved in the part and in the part that, in the humanization of its benefits, will also be endorsed the importance of the nursing professional in order to, in the end, discuss about how it conducts and procedures performed for the Nursing team. This is a quantitative literature review, where information published without a time lapse of 15 years (2007-202) was collected in the Google databases2 literature review. Regarding the objective of the research, it is possible to characterize it as an exploratory research, since the intention is to explore the subject in question, find connections and a deepening of the theme. Through the study carried out, it was possible to verify that the humanization of childbirth is a growing that deserves attention and training of nursing professionals, since it is a branch on the rise, the treatment of the health team must be, in any situation, the most human possible.